Beam Shift Modulation Based on Larmor Resonance in Graphene–VO2 Photonic Crystal. Issue 4 (13th February 2022) - Tang, Tingting; Li, Jun; Mao, Yinghui; Liu, Bo; Peng, Sui; Yu, Bo; Liang, Xiao; Luo, Li; Tang, Yujie; He, Ke
Abstract : A new method to enhance the beam shift of Goos–Hänchen (GH) effect in a 1D photonic crystal based on Larmor resonance in terahertz (THz) region is proposed. Larmor resonance can enhance the surface plasmon resonance (SPR) effect, which enhances the GH effect. A 1D photonic crystal with a graphene–VO2 periodic structure is designed. As a result of different states at different temperatures, the SPR effect of graphene–VO2 periodic structure photonic crystals will change. In this structure, Larmor resonance caused by a strong magnetic field perpendicular to the incident surface will resonate with surface plasmons. It is found that the strength of the magnetic field required to enhance SPR is relative to the frequency of electromagnetic waves and the Fermi level. The enhancement of the GH effect by the Larmor resonance theory provides a new way for us to measure strong magnetic fields. Abstract : Herein, a new method is proposed to enhance Goos–Hänchen (GH) effect in a 1D photonic crystal based on Larmor resonance. Larmor resonance enhances the surface plasmon resonance effect which enhances GH effect. This provides a new way for us to measure strong magnetic fields.